Applicability of sublevel caving to small-scale orebodies: design and mixing analysis from the Jama Bor mine - Stojanovic, M; Vojinović, I; Šabaz, D; Svrkota, I; Villa, D (Caving 2026: Proceedings of the Sixth International Conference on Block and Sublevel Caving, 2026)
This paper presents the application of the sublevel caving (SLC) mining method in the T4 orebody of the Jama Bor underground mine, with emphasis on dilution control and draw behaviour in a small, geometrically irregular deposit. The T4 orebody contains approximately 300,000 tonnes of ore, requiring a compact and carefully scaled SLC design. The adopted mining solution comprises a 3-level SLC layout adapted to the limited size of the deposit, irregular ore boundaries and constraints imposed by the existing underground infrastructure. The design explicitly addresses conditions that influence caving propagation, material mixing, dilution entry and ore recovery. Dilution and recovery were evaluated using a flow-based marker mixing assessment in the PCSLC module within GEOVIA Surpac. The analysis focused on material flow paths, orewaste interaction, level interaction, and the sensitivity of the response to draw strategy and geometry. The results indicate that controlled dilution and stable recovery can be achieved at a small scale when draw rules and layout geometry are aligned. The case study demonstrates that SLC can be applied beyond large orebodies and can represent a technically viable mining method for smaller and geometrically complex deposits.
Keywords: sublevel caving